If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.33(18x + -12) = 2(3x + -2) Reorder the terms: 0.33(-12 + 18x) = 2(3x + -2) (-12 * 0.33 + 18x * 0.33) = 2(3x + -2) (-3.96 + 5.94x) = 2(3x + -2) Reorder the terms: -3.96 + 5.94x = 2(-2 + 3x) -3.96 + 5.94x = (-2 * 2 + 3x * 2) -3.96 + 5.94x = (-4 + 6x) Solving -3.96 + 5.94x = -4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3.96 + 5.94x + -6x = -4 + 6x + -6x Combine like terms: 5.94x + -6x = -0.06x -3.96 + -0.06x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 -3.96 + -0.06x = -4 + 0 -3.96 + -0.06x = -4 Add '3.96' to each side of the equation. -3.96 + 3.96 + -0.06x = -4 + 3.96 Combine like terms: -3.96 + 3.96 = 0.00 0.00 + -0.06x = -4 + 3.96 -0.06x = -4 + 3.96 Combine like terms: -4 + 3.96 = -0.04 -0.06x = -0.04 Divide each side by '-0.06'. x = 0.6666666667 Simplifying x = 0.6666666667
| 12(x+2)=3(4x+2)+18 | | 3p^2-14=5 | | 3x^2-15x=12 | | 4-x=2x+1 | | 3x^2+23=18 | | n^2=dn | | (-1)/(9)b=-12 | | 32a^2=72 | | 9a^8-45a^5+3a^3= | | 15x^4-75x^2+60=0 | | -5w^2+51=6 | | 12-x^2=17 | | -6=(1)/(20)h | | 57-13+5q=85 | | m(m-4)=12 | | 16x=-100 | | 48=14+2n^2 | | 2h-1=10-9h^2 | | 3x-6-2x=3x+6 | | t^2-4=6t+8 | | 12x+6y=1800 | | 4.3x-3.7-5.3x=-2.0x-2.4 | | 5p=5p^2-10 | | -2.3=3y+0.7 | | 3h^2+2h-6=0 | | 15x^2-75x^2+60=0 | | 6x-3=4x-9 | | 5n^2-7n=1 | | 6b^7-4b^3+b+3b^2= | | x(4)+y=6 | | b^2=40-3b | | x/.25=7 |